AFIKS PEMBENTUK DERIVASIONAL BAHASA MINANGKABAU DIALEK AGAM KECAMATAN KAMANG MAGEK - Zeli, Silvia; ', Auzar; Faizah AR, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the formation of derivational affixes, derivational types of affixes forming and forming derivational affixes meaning that there is language Minangkabau dialect Kamang Magek Agam District. This study aimed to describe the formation of derivational affixes and change the meaning of words after the derivational language Minangkabau dialect Kamang Magek Agam District. Research theoretically and practically useful. This research is qualitative research and descriptive method. Techniques used in data collection techniques in this research that record, noting technique, fishing techniques, storytelling, inventasirasi data, classification data, and summarize data. The data have been found and analyzed in several stages, ie transcribing data, rewriting the data obtained, classifying data, analyzing data, and writing the results of the analysis. Data found derivational affixes derived from speech and folklore available where the study was conducted. The object of this study is language. The results of this study as a contribution to further research on derivational affixes.Key Words: Affix derivational, Minangkabau, Agam